O SOCIODRAMA: METODOLOGIA DE ENSINO NO APERFEIÇOAMENTO DE PROFESSORES DO NÍVEL SUPERIOR - HRUSCHKA, LUIZA CORREIA (2017)
This study aims to analyze usage of sociodramatic methodology to improve didactics of Administration undergraduate courses, according to their students’ profiles. The main themes of this research are: Education, Pedagogy and Didactics; Methodology and Didactics of Undergraduate Teaching; Teachers’ Formation and Continuous Development; Teaching-learning Process; Andragogy; Group Theory; Psychodrama and Sociodrama. In that order, a qualitative study with an exploratory approach and experimental aspects was chosen. The instrument used is the TREM – Transform, Highlight, Exclude and Maintain – which refers to an individual evaluation assessment that enables the participant to evaluate the sociodramatic class according to the following criteria: teacher’s posture in the classroom, understanding of the teaching-learning process, and the teacher’s perception about student’s behavior in the class. Nine undergraduate classes’ teachers took part in this study, which seven were from Administration area, one from Pedadogy area and the last one from Automation and High School areas. Collected data from the TREM instrument were divided according to the evaluation criteria in order to improve reader’s understanding about the study. The research concludes that usage of sociodramatic methodology changes the studied teachers’ didactics, since 56% of their difficulties are related do dispersion, disinterest and demotivation, and applying this methodology makes the students more participative and interested in classes, turning them into part of the teaching-learning process. An important result related to the methodology usage is that teachers stimulates students’ participation, improve their listening, includes practical activities, better time management and bigger compliance to proposed program. Relating to teaching-learning process, the students becomes active subject of the process, their experiences are valued, it becomes possible to identify and correct their difficulties, and it highlights teamwork towards developing cooperative construction skills and interpersonal relationships. About the student behavior in the classroom, it becomes protagonist, gains responsibilities and lowers cellphone usage and parallel conversations, since its needed to experience classroom steps, and gives more ease to perform practical activities. As a challenge, for future studies, it needs to improve usage of techniques directed to the stages that compose the sociodramatic classes, mainly, for those teachers who frequently use expository techniques. Another challenge to consider is the technique of dramatization in the teaching-learning process, based on the sociodramatic methodology, which deserves a greater emphasis.